P214 Utilisation Of Cardio-pulmonary Exercise Testing (cpet) At An English Acute Hospital. (10th November 2014) - Parkes, E; Moore, VC; Comer, D; Rauf, F; Santana-Vaz, N; Mukherjee, R
Abstract : Background: CPET has been extensively used in the pre-operative (general anaesthesia) risk stratification. More recently, the utility of CPET has become more defined in the evaluation of unexplained dyspnoea and in prognosticating pulmonary hypertension in a rational manner which is also less invasive for patients. We set out to evaluate the utilisation pattern of CPET within a 709-bedded central England acute hospital Trust spread across 3 sites in the second year of the establishment of the service. Methods: The source of referral (and reason) for CPET were retrospectively recorded and analysed between 01 July 2013 and 31 May 2014 (ten months). Results: The total number of CPET referrals received was 178 out of which 150 (84%) were from surgical disciplines and 28 (16%) from medical disciplines. Vascular surgery submitted made the majority of referrals (108, 61%) followed by colorectal surgery [see Figure ]. Respiratory Medicine was the source of 11% of all referrals and Cardiology the source of 4%. Conclusions: The dominant utilisation of CPET by vascular surgery is expected, given the NHS evidence adoption centre and National Institute for Health and Care Excellence (NICE) 2009 recommendations on risk-stratification for Abdominal Aortic Aneurysm surgery mortality. However, CPET offers a unique assessment tool for the investigation of patients with unexplained dyspnoea and has a potential to pre-empt invasive, unnecessary and expensive assessment without definitive diagnosis [Thing JER, Mukherjee B, Murphy K et al . Thorax 2011; 66 (4): A144]. It appears that a lot of work needs to be done among the UK general respiratory and cardiology/heart failure communities to promote the awareness, understanding and utilisation of CPET.